PARAPROSTHETIC RECURRENT VENTRAL HERNIAS AND THEIR SURGICAL CORRECTION - Akmal Aliyarovich, Khaitov; Ishnazar Boynazarovich, Mustafakulov (Journal of Medical Genetics and Clinical Biology, 2024)
Objective: To conduct a comparative analysis of macro- and microscopic morphological changes in tissues in patients with recurrent ventral hernias and to improve surgical methods for managing these cases. Methods: Patients were divided into two groups based on prior hernioplasty techniques: Group I (n=52) received tension methods, while Group II (n=26) underwent non-tension prosthetic methods. Clinical and instrumental analyses, including CT scans and morphological assessments of tissue around prostheses, were performed to evaluate recurrence patterns and inflammation levels. Results: Findings revealed that complete relapses frequently followed tension hernioplasty, while non-tension methods resulted in partial recurrences along the prosthesis contours. Tension methods showed significant void formation and inflammatory responses around the prostheses, while non-tension techniques led to a mature connective tissue response. The recurrence rate was notably lower (3.8%) in patients treated with improved non-tension methods, such as "onlay" without defect suturing and "onlay + sublay" with duplication. Novelty: This study offers insights into morphological differences in tissue responses based on hernioplasty techniques, supporting improved surgical methods for recurrent hernias. By enhancing tension-free techniques, recurrence rates were reduced from 15% to 3.8%, underscoring the clinical benefit of tailored approaches in recurrent ventral hernia management.